Responsible innovation: From MOOC to book - Groot Kormelink, Joost; Kaliarnta, Sofia; Srivatsa, N. (2018)
THIS IS THE FIRST EDITION, ONLY AVAILABLE ON REQUEST. PLEASE CONTACT EducationsupportTHE 2ND EDITION IS AVAILABLE HEREInnovation may bring a lot of good to society, but innovation is not a good in itself. Historyprovides many examples of innovations and new technologies that have had serious negativeconsequences, or that just failed to address significant problems and make meaningfulcontributions to society; recall for example carcinogenic asbestos or the ecological devastationof DDT.At the same time, we do need new technologies to find solutions for grand societal challengessuch as energy scarcity, ageing demographics, water management and/or food security. Sowe are looking for responsible innovation in multiple upcoming fields that demand urgentattention in this regard: nanotechnology, biotechnology, artificial intelligence, policy-makingbased on big data analytics, and so on.Our goal then is to give you an in-depth knowledge of what responsible innovation entails - anethical perspective to help shape socio-technical solutions for global and regional problems.This reader is intended to give a comprehensive but by no means exhaustive primer toresponsible innovation. Responsible Innovation (abbreviated as RI henceforth) is a broad termthat refers to the acts of analysis, reflection and public debate concerning the ethical principlesand moral acceptability of new and emerging technologies.To do this, we must be able to answer key questions such as these:1. Do our efforts in applied science, technology and engineering contribute to the solution ofthe big problems of our age?2. How do we find solutions for global problems in a responsible way?3. Can technical solutions accommodate the plurality of moral values and the needs of allparties affected?The term “Responsible Innovation” itself was first introduced in 2006 in the context of theDutch Research Council Program entitled Socially Responsible Innovations.: it is now incorporated into the larger Research and Development agenda of the European Union (EU).As recently as November 2014, the policy was endorsed and extended in the RomeDeclaration on Responsible Research and Innovation.While thinking about RI has its roots in Europe, it is a concept with a true global reach.Consider that we live in a hyper-connected world: science provides knowledge of thefundamental building blocks and processes in Nature, our technologies scarcely leave anyresource on the planet untouched. So, it is of the utmost importance, our duty even, to definean adequate and shared conception of responsibility for our innovations and technologies.Can our innovations save lives? Will they produce more jobs? Can they save the planet, oronly contribute more waste and pollution? Are they safe for users and secure from abusers?Do they respect values and basic human rights we hold dear, like privacy, freedom, autonomyand equality? If not, how can we make them so? If not us, who? If not now, when?